The Dynamics of Dirty Dozen Human Errors in ATC Training Simulations Under Unusual Conditions - Dimas Arya Soeadyfa Fridyatama; Farid Baskoro; Yuyun Suprapto; Wachidah Ramadhanty Putri (Universitas Trunodjoyo Madura, 2025)
This study investigates the dynamics of Dirty Dozen human error factors within Air Traffic Control (ATC) training simulations conducted under unusual conditions such as emergencies, urgency events, and communication failures. Using a Grounded Theory approach, data were collected from 13 cadets of the Aerodrome Control Tower program at the Surabaya Aviation Polytechnic through participatory observation, in-depth interviews, and supporting documentation. The analysis employed open coding, axial coding, and selective coding, leading to the construction of a conceptual model that explains the emergence and interaction of Dirty Dozen factors. Findings reveal that these factors often arise simultaneously and reinforce one another, primarily triggered by operational pressure, limited resources, and insufficient preparedness in non-technical skills. Contextual elements within the learning environment—such as informal norms and technical limitations of the simulator—also intensified the occurrence of errors. Despite these challenges, cadets demonstrated adaptive strategies including communication adjustments, teamwork improvisation, and stress management techniques. The study highlights the systemic and dynamic nature of Dirty Dozen factors and underscores the need to integrate non-technical skill development into ATC training programs to strengthen human error mitigation from the early stages of professional education.